End Group Tuning in Acceptor–Donor–Acceptor Nonfullerene Small Molecules for High Fill Factor Organic Solar Cells. (11th June 2019) - Wadsworth, Andrew; Bristow, Helen; Hamid, Zeinab; Babics, Maxime; Gasparini, Nicola; Boyle, Colm W.; Zhang, Weimin; Dong, Yifan; Thorley, Karl. J.; Neophytou, Marios; Ashraf, Raja Shahid; Durrant, James R.; et al.
Abstract: High fill factors have only recently become commonplace in nonfullerene‐based organic solar cells, with the balance of charge carrier mobilities often cited as the contributing factor. Here an end‐group modification to a commonly used nonfullerene acceptor (O‐IDTBR) is reported, in which the rhodanine end groups are replaced with dicyano moieties, resulting in the acceptor O‐IDTBCN. This new acceptor affords significant improvement in the fill factor (73%) and photocurrent (19.8 mA cm −2 ) in organic solar cells with the low bandgap polymer PTB7‐Th. A narrowing of the bandgap, as a result of greater push–pull hybridization, allows complementary absorption to the donor and thus improved photon harvesting. Additionally, the measurement of charge carrier mobilities and lifetimes in both systems reveal that the PTB7‐Th:O‐IDTBCN blend possesses more balanced charge carrier mobilities, and longer lifetimes. Morphology studies reveal a slightly greater degree of molecular mixing of the O‐IDTBCN when blended with PTB7‐Th, despite the greater and more balanced charge carrier mobilities in this blend. Abstract : O‐IDTBCN is a new nonfullerene acceptor that uses dicyanovinyl end groups to improve the electron mobility in blends with PTB7‐Th, relative to its predecessor, O‐IDTBR. Blends with O‐IDTBCN possess more balanced charge carrier mobilities, resulting in longer charge carrier lifetimes, which ultimately manifests in the attainment of fill factors of over 70% in devices.